7 T Magnetic Resonance Spectroscopic Imaging in Multiple Sclerosis: How Does Spatial Resolution Affect the Detectability of Metabolic Changes in Brain Lesions?. Issue 4 (April 2019) - Heckova, Eva; Strasser, Bernhard; Hangel, Gilbert J.; Považan, Michal; Dal-Bianco, Assunta; Rommer, Paulus S.; Bednarik, Petr; Gruber, Stephan; Leutmezer, Fritz; Lassmann, Hans; Trattnig, Siegfried; Bogner, Wolfgang
Abstract : Objectives: The aim of this study was to assess the utility of increased spatial resolution of magnetic resonance spectroscopic imaging (MRSI) at 7 T for the detection of neurochemical changes in multiple sclerosis (MS)–related brain lesions. Materials and Methods: This prospective, institutional review board–approved study was performed in 20 relapsing-remitting MS patients (9 women/11 men; mean age ± standard deviation, 30.8 ± 7.7 years) after receiving written informed consent. Metabolic patterns in MS lesions were compared at 3 different spatial resolutions of free induction decay MRSI with implemented parallel imaging acceleration: 2.2 × 2.2 × 8 mm 3 ; 3.4 × 3.4 × 8 mm 3 ; and 6.8 × 6.8 × 8 mm 3 voxel volumes, that is, matrix sizes of 100 × 100, 64 × 64, and 32 × 32, respectively. The quality of data was assessed by signal-to-noise ratio and Cramér-Rao lower bounds. Statistical analysis was performed using Wilcoxon signed-rank tests with correction for multiple testing. Results: Seventy-seven T2-hyperintense MS lesions were investigated (median volume, 155.7 mm 3 ; range, 10.8–747.0 mm 3 ). The mean metabolic ratios in lesions differed significantly between the 3 MRSI resolutions (ie, 100 × 100 vs 64 × 64, 100 × 100 vs 32 × 32, and 64 × 64 vs 32 × 32; P < 0.001). With the ultra-high resolution (100 × 100), we obtained 40% to 80% higher mean metabolic ratios and 100% to 150% increase in maximum metabolic ratios in the MS lesions compared with the lowest resolution (32 × 32), while maintaining good spectral quality (signal-to-noise ratio >12, Cramér-Rao lower bounds <20%) and measurement time of 6 minutes. There were 83% of MS lesions that showed increased myo -inositol/ N -acetylaspartate with the 100 × 100 resolution, but only 66% were distinguishable with the 64 × 64 resolution and 35% with the 32 × 32 resolution. Conclusions: Ultra-high-resolution MRSI (~2 × 2 × 8 mm 3 voxel volume) can detect metabolic alterations in MS, which cannot be recognized by conventional MRSI resolutions, within clinically acceptable time. Abstract : Supplemental digital content is available in the text.